Conical intersections: electronic structure, dynamics & spectroscopy - Domcke, Wolfgang; Yarkony, David; Köppel, Horst (Advanced series in physical chemistry, 2004)
Part III. Detection and control of chemical dynamics at conical intersections.Absorption, emission, and photoelectron continuous-wave spectra /A. Lami, C. Petrongolo, F. Santoro --Femtosecond time-resolved spectroscopy of the dynamics at conical intersections /G. Stock, W. Domcke --Nonadiabatic quantum dynamics and control strategies /R. de Vivie-Riedle, A. Hofmann.
Includes bibliographical references and index. - Description based on print version record
Keywords: Electronic books; Spektroskopie; Elektronenstruktur; Potenzialhyperfläche